Self-lubricating nano ceramic composite grinding ball and preparation method thereof
By uniformly dispersing self-lubricating nanoceramic particles in the grinding ball and performing specific heat treatment and additive optimization, the problem of easy wear and fracture of traditional grinding balls under high impact loads is solved, and the wear resistance and impact toughness of grinding balls is significantly improved. , reduces friction coefficient and energy consumption, extends service life, and meets the needs of energy conservation and consumption reduction.
Patent Information
- Application Number
- CN202411623725.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional grinding balls are prone to wear and break under high impact loads, have a short service life, frequent replacement increases maintenance costs, and the high friction coefficient leads to large energy loss, which cannot meet the energy saving and consumption reduction needs.
Self-lubricated nanoceramic composite grinding balls are used, which contain matrix materials and uniformly dispersed self-lubricated nanoceramic particles. The microstructure structure is optimized through specific heat treatment processes and additives to improve the wear resistance and impact toughness of grinding balls.
It significantly improves the hardness and wear resistance of the grinding ball, reduces the friction coefficient, reduces wear and energy consumption, extends the service life of the grinding ball, reduces maintenance costs and energy consumption, and meets the needs of energy saving and consumption reduction.
Smart Images

Figure CN119456950A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grinding ball preparation, in particular to a self-lubricating nano ceramic composite grinding ball and a preparation method thereof. Background Art
[0002] Grinding ball preparation refers to the process of producing grinding media (i.e., grinding balls) used in ball mills. These grinding balls achieve material crushing and refinement through collision and friction with the materials in the ball mill. The preparation process of grinding balls usually includes multiple steps such as material selection, smelting, casting, heat treatment, and surface treatment. However, traditional grinding balls are prone to wear and breakage under high impact loads, especially in heavy industrial fields such as large mines and cement plants. The service life of grinding balls is short, and frequent replacement increases maintenance costs. In addition, due to the high friction coefficient of traditional grinding balls during the grinding process, energy loss is large, which increases production costs and does not meet the needs of energy conservation and consumption reduction. At the same time, due to the poor wear resistance and impact resistance of traditional grinding balls, they need to be replaced frequently, which increases downtime and maintenance costs, affecting production continuity and economic benefits. Summary of the invention
[0003] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] A self-lubricating nano-ceramic composite grinding ball and a preparation method thereof, wherein the grinding ball comprises a matrix material and self-lubricating nano-ceramic particles uniformly dispersed therein, wherein the self-lubricating nano-ceramic particles are selected from at least one of boron nitride, graphene or molybdenum disulfide, and the mass percentage of the self-lubricating nano-ceramic particles in the grinding ball is 0.5% to 20%, preferably 1% to 10%;
[0006] The matrix material includes, but is not limited to, high chromium cast iron, low carbon steel or ausferrous ductile iron, and the matrix material has a hardness of at least 800 HB.
[0007] As a further solution of the present invention: the self-lubricating nano-ceramic particles have an average particle size of less than 1 micron, preferably less than 0.5 micron, and the surface is modified with a silane coupling agent to enhance the interface bonding force with the matrix material, thereby improving the overall strength and wear resistance of the composite material.
[0008] As a further solution of the present invention: the grinding ball also contains additives, including but not limited to cemented carbide particles such as tungsten carbide, rare earth elements such as cerium or lanthanum, and metal oxides such as aluminum oxide, to further improve the wear resistance and impact toughness of the grinding ball, and the total mass percentage of the additives does not exceed 10% of the total mass of the grinding ball.
[0009] As a further solution of the present invention: the grinding ball is subjected to a specific heat treatment process to obtain an optimized microstructure, and the heat treatment process includes isothermal quenching continuous cooling and waste heat air isothermal treatment steps, wherein the isothermal quenching temperature ranges from 700°C to 900°C, the holding time is 1 hour to 3 hours, and then naturally cooled to room temperature in air.
[0010] A preparation method, according to the self-lubricating nano-ceramic composite grinding ball according to any one of claims 1 to 4, characterized in that the method comprises the following steps:
[0011] Melting the base material to a completely liquid state;
[0012] Add pretreated self-lubricating nano-ceramic particles to the molten matrix material and mix them thoroughly by mechanical stirring or ultrasonic vibration to ensure uniform distribution of the particles;
[0013] Casting in a protective atmosphere, in an inert gas (argon or nitrogen) environment;
[0014] The obtained grinding ball semi-finished product is subjected to the above-mentioned specific heat treatment process.
[0015] As a further solution of the present invention: the method also includes the step of pretreating the surface of the self-lubricating nano-ceramic particles, and the pretreatment method includes a chemical plating method, that is, immersing the nano-particles in a solution containing a silane coupling agent, reacting for a certain period of time and then drying, or a physical vapor deposition method, in which an organic silicon compound is evaporated onto the surface of the nano-particles under vacuum conditions to form a protective film.
[0016] As a further solution of the present invention: a multi-cycle quenching-carbon distribution-isothermal treatment process is adopted in the heat treatment process, each cycle includes rapid heating to the quenching temperature, holding for a period of time and then rapidly cooling to room temperature, then slowly heating to a lower temperature for carbon distribution, and finally isothermal treatment at this temperature for a period of time. The microstructure of the grinding ball is optimized by adjusting the time and temperature parameters of each stage, especially increasing the proportion of martensite phase to improve hardness and toughness.
[0017] As a further embodiment of the present invention, the method further comprises performing subsequent processing on the surface of the grinding ball, such as mechanical polishing to remove surface defects, or applying a corrosion-resistant coating, such as electroplating a nickel-phosphorus alloy coating or spraying a polytetrafluoroethylene coating, to improve the surface quality and corrosion resistance.
[0018] As a further solution of the present invention: the grinding balls exhibit excellent self-lubricating properties during the ball milling process, effectively reducing the friction coefficient, reducing the energy consumption of the mill, while improving the grinding efficiency and extending the service life of the grinding balls, especially under dry grinding conditions.
[0019] As a further solution of the present invention: the grinding balls can withstand high-intensity impact loads without obvious plastic deformation or fracture, and can maintain stable service performance even under extreme working conditions. They are particularly suitable for grinding equipment in large mines, cement plants and other heavy industrial fields.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] By evenly dispersing self-lubricating nano-ceramic particles in the matrix material and adding cemented carbide particles, rare earth elements and metal oxides, the hardness and wear resistance of the grinding balls are significantly improved. The presence of self-lubricating nano-ceramic particles enables the grinding balls to provide continuous lubrication during the grinding process, effectively reducing the friction coefficient, reducing wear and energy consumption. Since the wear resistance and impact resistance of the grinding balls have been significantly improved, the frequency of replacing the grinding balls is reduced, and the downtime and maintenance costs are reduced. Since the friction coefficient is reduced, the energy loss is reduced, which helps to reduce the overall energy consumption of the ball mill and meets the needs of energy saving and consumption reduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The present invention is a schematic diagram of the operation flow of a self-lubricating nano-ceramic composite grinding ball and a preparation method thereof. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings.
[0024] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0025] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0026] Example 1
[0027] See also Figure 1 , which is the first embodiment of the present invention, provides a high chromium cast iron matrix + boron nitride nanoparticles, specifically as follows:
[0028] Raw material preparation:
[0029] Base material: high chromium cast iron (hardness 800HB);
[0030] Self-lubricating nano-ceramic particles: boron nitride (BN), average particle size 0.3 microns;
[0031] Additives: tungsten carbide (WC) particles, cerium (Ce);
[0032] step:
[0033] Matrix material melting:
[0034] The high chromium cast iron is melted in an electric arc furnace until it is completely liquid, at a temperature of about 1500°C;
[0035] Self-lubricating nano-ceramic particle pretreatment:
[0036] The boron nitride nanoparticles were immersed in a solution containing a silane coupling agent (KH550), stirred evenly, reacted at 60°C for 4 hours, and then dried at 100°C for 2 hours;
[0037] Adding self-lubricating nano-ceramic particles:
[0038] The pretreated boron nitride nanoparticles were added into the molten high chromium cast iron at a mass percentage of 3%;
[0039] Use an ultrasonic vibrator to mix thoroughly to ensure that the nanoparticles are evenly dispersed;
[0040] Additives added:
[0041] Add tungsten carbide particles (5% by mass) and cerium (0.5% by mass) to the mixture and stir again;
[0042] Casting:
[0043] The mixture was cast into grinding ball blanks of standard size under argon protective atmosphere;
[0044] Heat Treatment:
[0045] Isothermal quenching, continuous cooling and isothermal treatment with residual heat air: heat to 850℃, keep warm for 2 hours, then quickly cool to room temperature; then slowly heat to 700℃ for carbon distribution, keep for 1 hour, and finally cool naturally to room temperature in air;
[0046] Subsequent processing:
[0047] Mechanically polish the surface of the grinding ball to remove surface defects;
[0048] Improve surface quality and corrosion resistance by electroplating nickel-phosphorus alloy coating;
[0049] Test results:
[0050] Wear resistance test: The test was carried out using a standard wear tester, and the results showed that the wear rate of the grinding ball was 30% lower than that of the traditional high chromium cast iron grinding ball;
[0051] Impact toughness test: Charpy impact test was used, and the results showed that the impact toughness of the grinding ball increased by 20%;
[0052] Friction coefficient test: Under dry grinding conditions, the friction coefficient of the grinding ball is reduced by 25%, significantly reducing the energy consumption of the mill;
[0053] Service life test: In actual mining applications, the service life of this grinding ball is about 20% longer than that of traditional grinding balls.
[0054] Example 2
[0055] See also Figure 1 , which is the second embodiment of the present invention, and provides an ausferrite ductile iron matrix + graphene nanoparticles, specifically as follows:
[0056] Raw material preparation:
[0057] Base material: ausferrous ductile iron (hardness 800HB);
[0058] Self-lubricating nano-ceramic particles: graphene, average particle size 0.4 microns;
[0059] Additives: Alumina (Al2O3), Lanthanum (La);
[0060] step:
[0061] Matrix material melting:
[0062] Ausferitic ductile iron is melted in an induction furnace until it is completely liquid at a temperature of about 1450°C;
[0063] Self-lubricating nano-ceramic particle pretreatment:
[0064] By physical vapor deposition, an organic silicon compound is evaporated onto the surface of graphene nanoparticles under vacuum conditions to form a protective film;
[0065] Adding self-lubricating nano-ceramic particles:
[0066] The pretreated graphene nanoparticles were added into molten ausferrous ductile iron at a mass percentage of 5%.
[0067] Use a mechanical stirrer to mix thoroughly to ensure that the nanoparticles are evenly dispersed;
[0068] Additives added:
[0069] Add alumina particles (4% by mass) and lanthanum (0.3% by mass) to the mixture and stir again;
[0070] Casting:
[0071] Under a nitrogen protective atmosphere, the mixture is cast into grinding ball blanks of standard size;
[0072] Heat Treatment:
[0073] Multi-cycle quenching-carbon distribution-isothermal treatment: Each cycle includes rapid heating to 900℃, holding for 1.5 hours, and rapid cooling to room temperature; then slowly heating to 750℃ for carbon distribution, holding for 1 hour, and finally isothermal treatment at this temperature for 1 hour, for a total of three cycles;
[0074] Subsequent processing:
[0075] Mechanically polish the surface of the grinding ball to remove surface defects;
[0076] Improve surface quality and corrosion resistance by spraying PTFE coating;
[0077] Test results:
[0078] Wear resistance test: The test was conducted using a standard wear tester, and the results showed that the wear rate of the grinding ball was 25% lower than that of the traditional austinite ductile iron grinding ball;
[0079] Impact toughness test: Charpy impact test was used, and the results showed that the impact toughness of the grinding ball increased by 15%;
[0080] Friction coefficient test: Under dry grinding conditions, the friction coefficient of the grinding ball is reduced by 20%, significantly reducing the energy consumption of the mill;
[0081] Service life test: In actual cement plant applications, the service life of this grinding ball is about 18% longer than that of traditional grinding balls.
[0082] In summary, the two examples show that the wear resistance, impact toughness and self-lubricating properties of the grinding balls can be significantly improved through different material combinations and preparation processes. Specifically:
[0083] Wear resistance: The wear resistance of the grinding balls has been significantly improved by adding self-lubricating nano-ceramic particles and optimizing the heat treatment process;
[0084] Impact toughness: Adding specific additives and optimizing the microstructure improves the impact toughness of the grinding balls;
[0085] Self-lubricating property: The presence of self-lubricating nano-ceramic particles makes the grinding balls exhibit excellent self-lubricating properties during the grinding process, effectively reducing the friction coefficient and energy consumption;
[0086] Service life: Through the above improvements, the service life of the grinding balls is significantly extended, thereby reducing maintenance costs and the risk of production interruptions.
[0087] Importantly, it should be noted that the construction and arrangement of the present application shown in a plurality of different exemplary embodiments are only exemplary. Although only a few embodiments are described in detail in this disclosure, it should be readily understood by those who refer to this disclosure that many modifications are possible (e.g., the size, scale, structure, shape and proportion of various elements, and parameter values (e.g., temperature, pressure, etc.), installation arrangement, use of materials, color, directional changes, etc.) without substantially departing from the novel teachings and advantages of the subject matter described in the application. For example, the element shown as integrally formed can be composed of multiple parts or elements, the position of the element can be inverted or otherwise changed, and the nature or number or position of the discrete element can be changed or changed. Therefore, all such modifications are intended to be included in the scope of the present invention. The order or sequence of any process or method steps can be changed or reordered according to alternative embodiments. In the claims, any "device plus function" clause is intended to cover the structure of performing the function described herein, and is not only structurally equivalent but also equivalent structure. Without departing from the scope of the present invention, other replacements, modifications, changes and omissions can be made in the design, operating conditions and arrangement of the exemplary embodiments. Therefore, the invention is not limited to a specific embodiment, but extends to numerous modifications still falling within the scope of the appended claims.
[0088] Additionally, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment (ie, those features that are not relevant to the best mode presently contemplated for carrying out the invention or those that are not relevant to implementing the invention) may not be described.
[0089] It will be appreciated that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but will be a routine task of design, fabrication, and production for those of ordinary skill having the benefit of this disclosure without undue experimentation.
[0090] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A self-lubricating nano-ceramic composite grinding ball, characterized in that: The grinding ball comprises a matrix material and self-lubricating nano-ceramic particles uniformly dispersed therein, wherein the self-lubricating nano-ceramic particles are selected from at least one of boron nitride, graphene or molybdenum disulfide, and the mass percentage of the self-lubricating nano-ceramic particles in the grinding ball is 0.5% to 20%, preferably 1% to 10%; The matrix material includes, but is not limited to, high chromium cast iron, low carbon steel or ausferrous ductile iron, and the matrix material has a hardness of at least 800 HB.
2. The self-lubricating nano-ceramic composite grinding ball according to claim 1, characterized in that: The self-lubricating nano-ceramic particles have an average particle size of less than 1 micron, preferably less than 0.5 micron, and the surface is modified by a silane coupling agent to enhance the interface bonding force with the matrix material and improve the overall strength and wear resistance of the composite material.
3. The self-lubricating nano-ceramic composite grinding ball according to claim 1, characterized in that: The grinding ball also contains additives, including but not limited to cemented carbide particles such as tungsten carbide, rare earth elements such as cerium or lanthanum, and metal oxides such as aluminum oxide, to further improve the wear resistance and impact toughness of the grinding ball. The total mass percentage of the additives does not exceed 10% of the total mass of the grinding ball.
4. The self-lubricating nano-ceramic composite grinding ball according to claim 1, characterized in that: The grinding ball is subjected to a specific heat treatment process to obtain an optimized microstructure, and the heat treatment process includes isothermal quenching continuous cooling and waste heat air isothermal treatment steps, wherein the isothermal quenching temperature ranges from 700°C to 900°C, the holding time is 1 hour to 3 hours, and then naturally cooled to room temperature in air.
5. A preparation method, according to the self-lubricating nano-ceramic composite grinding ball according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: Melting the base material to a completely liquid state; Add pretreated self-lubricating nano-ceramic particles to the molten matrix material and mix them thoroughly by mechanical stirring or ultrasonic vibration to ensure uniform distribution of the particles; Casting in a protective atmosphere and in an inert gas environment; The obtained grinding ball semi-finished product is subjected to the above-mentioned specific heat treatment process.
6. A preparation method according to claim 5, characterized in that: The method also includes the step of pretreating the surface of the self-lubricating nano-ceramic particles, and the pretreatment method includes a chemical plating method, that is, immersing the nano-particles in a solution containing a silane coupling agent for a certain reaction time and then drying, or a physical vapor deposition method, in which an organic silicon compound is evaporated onto the surface of the nano-particles under vacuum conditions to form a protective film.
7. A preparation method according to claim 5, characterized in that: The heat treatment process adopts a multi-cycle quenching-carbon distribution-isothermal treatment process, each cycle includes rapid heating to the quenching temperature, holding for a period of time and then rapidly cooling to room temperature, then slowly heating to a lower temperature for carbon distribution, and finally isothermal treatment at this temperature for a period of time. The microstructure of the grinding ball is optimized by adjusting the time and temperature parameters of each stage, especially increasing the proportion of the martensite phase to improve the hardness and toughness.
8. A preparation method according to claim 5, characterized in that: The method also includes performing subsequent processing on the surface of the grinding ball, such as mechanical polishing to remove surface defects, or applying a corrosion-resistant coating, such as electroplating a nickel-phosphorus alloy coating or spraying a polytetrafluoroethylene coating, to improve the surface quality and corrosion resistance.
9. A self-lubricating nano-ceramic composite grinding ball according to any one of claims 1 to 8, characterized in that: The grinding balls exhibit excellent self-lubricating properties during ball milling, effectively reduce the friction coefficient, reduce the energy consumption of the mill, and at the same time improve the grinding efficiency and extend the service life of the grinding balls, especially under dry grinding conditions.
10. A self-lubricating nano-ceramic composite grinding ball according to any one of claims 1 to 9, characterized in that: The grinding balls can withstand high-intensity impact loads without significant plastic deformation or fracture, and can maintain stable service performance even under extreme working conditions. They are particularly suitable for grinding equipment in large mines, cement plants and other heavy industrial fields.
Citation Information
Cited By
Double-barrier self-lubricating anti-coking composite coating and preparation method thereof
CN120485681A